Liquid Chromatographic Isolation of Individual Amino Acids Extracted From Sediments for Radiocarbon Analysis - Blattmann, Thomas M.; Montluçon, Daniel B.; Haghipour, Negar; Ishikawa, Naoto F.; Eglinton, Timothy I. (Frontiers in Marine Science, 2020)
The “building blocks of life” are found nearly ubiquitously in the environment in the form of proteins, peptides, and single amino acids. To shed light on amino acid sources, cycling, and preservation in sedimentary environments, we present a method using high-pressure liquid chromatography to separate and isolate underivatized amino acids extracted from sediments to conduct compound-specific radiocarbon analysis. This method consists of three main steps including (1) amino acid extraction by hydrofluoric and hydrochloric acids followed by desalting, (2) liquid chromatographic isolation and purification using two complementary column chemistries, and (3) post-purification and measurement by accelerator mass spectrometry. The resulting blank of this procedure is estimated to contain 2.2 ± 1.3 μgC with 0.25 ± 0.09 Fm.